라이브 커머스의 IT 어포던스가 상호작용성과 몰입감, 구매 의도에 미치는 영향 - 주은신(Eunsin Joo) (한국콘텐츠학회 논문지, 22(2), 2022)
Live streaming is becoming increasingly popular as it is distributed through various platforms around the world. In particular, after the outbreak of the COVID-19, it has shown unprecedented growth in the domestic e-commerce sector. Building a theoretical model from the perspective of IT affordance, this study aims to examine how live streaming affordance influences users' purchase intentions through perceived interactivity and immersion. An online survey was conducted among South Koreans who had experience using live streaming commerce. Our results show that IT affordance, such as visibility, metavoicing, guidance shopping, had positive effects on purchase intentions through the serial mediation effects of perceived interactivity and immersion. Our study highlights the importance of understanding theoretical and practical implications of IT affordance for live streaming commerce. 실시간 온라인 방송이 다양한 플랫폼을 통해 보급되면서 전 세계적으로 큰 인기를 끌고 있다. 특히 코로나 19 대유행으로 인해 사회적 거리두기가 시행됨에 따라 국내 온라인 쇼핑 분야에서 전례 없는 성장세를 보여주고 있다. 본 연구는 IT 어포던스의 관점에서 라이브 커머스의 디지털 플랫폼 차원의 기술 어포던스 특성이 이용자의 상호작용성과 몰입감을 매개로 구매 의도에 어떠한 영향을 미치는지를 살펴보고자 했다. 이를 위해, 국내 라이브 커머스 이용 경험자 440명을 대상으로 온라인 설문조사를 실시하였다. 수집된 자료는 확인적 요인분석과 구조방정식모형을 실시하여 분석하였다. 연구 결과 플랫폼의 메타보이싱과 쇼핑가이드 특성을 높게 인지할수록 이용자의 상호작용성은 높아지는 것으로 나타났다. 또한, 제품에 관한 가시성이 뛰어나다고 느낄수록 이용자는 쇼핑 상황에 더 몰입하는 것으로 밝혀졌다. 나아가 상호작용성과 몰입감은 매개 변수로서 IT 어포던스 특성이 구매 의도에 미치는 영향에 중요한 역할을 수행하는 것으로 나타났다. 본 연구의 결과를 바탕으로 라이브 커머스 마케팅 전략 수립을 위한 이론적·실무적 시사점을 제시하였다.